SYNTHESIS, STRUCTURAL CHARACTERIZATION AND PHOTOCATALYTIC ACTIVITY OF TIO2 NANOPARTICLES - BESSI, ASSIA; BOUDINE, B; BOUDAREN, C (Courrier du Savoir, 2018)
Titanium dioxide (TiO 2 ) nanoparticles were synthesized via sol-gel process (soft chemistry), using the metal alkoxide as precursor.  TiO 2 is a promising material especially when it is reduced to the nanometric scale, but many parameters influence its nanoscale synthesis. In this work, the influence of calcination time was studied. The structure, morphology and size of the synthesized particles were determined by X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The XRD diffractograms revealed an anatase structure of the as prepared TiO 2 , with a nanometric size. The average particle size of TiO 2 , synthesized in ethanol as a solvent, is estimated to be 17 nm. An increase of calcination time induced an increase of the particle size to 21 nm, while keeping the anatase phase unchanged. FTIR measurements confirmed the pure anatase phase of TiO 2 and the SEM micrographs displayed the aggregation of the nanoscale particles. The photocatalytic activity of synthesized nanoparticles was investigated by degradation of  methylene blue dye by TiO 2 nanoparticles under ultraviolet radiation.